The globalization of business and the Middle East : opportunities and constraints - Kavoossi, Masoud (Quorum, 2000)
A study of the business, marketing, banking, economic integration and management practices of the Middle East. It examines the current sociocultural forces that impact the regional business environment, with a particular focus on globalization.